GE_GERICHTE P/11659/2012 vom 8. Februar 2017 - GE Cour de justice (2017)
DIFFAMATION ; PLAINTE PÉNALE ; DÉLAI ; BONNE FOI SUBJECTIVE ; EXCUSABILITÉ ; FIXATION DE LA PEINE ; PEINE PÉCUNIAIRE ; INDEMNITÉ(EN GÉNÉRAL) | CPP.139; CP.31; CP.173; CP.34; CP.47